2022
DOI: 10.1039/d2nj00861k
|View full text |Cite
|
Sign up to set email alerts
|

The crystalline state of rubrene materials: intermolecular recognition, isomorphism, polymorphism, and periodic bond-chain analysis of morphologies

Abstract: A survey of all crystal structures of rubrene materials in the Cambridge Structural Database is presented. Although the chemical substitution landscape is wide, hydrogen bonding functionalities are absent. Recognition motifs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…While the triclinic form retains the planar backbone, it packs in a brick-like arrangement, which has been shown with rubrene to have significantly reduced charge mobility (Matsukawa et al, 2010). This is a similar case to the NO 2 -substituted rubrene derivative [5,11-bis(4-nitrophenyl)-6,12-biphenyltetracene] in which the monoclinic form was discovered (Uttiya et al, 2014), with the triclinic reported later (Moret & Gavezzotti, 2022).…”
Section: Database Surveymentioning
confidence: 68%
“…While the triclinic form retains the planar backbone, it packs in a brick-like arrangement, which has been shown with rubrene to have significantly reduced charge mobility (Matsukawa et al, 2010). This is a similar case to the NO 2 -substituted rubrene derivative [5,11-bis(4-nitrophenyl)-6,12-biphenyltetracene] in which the monoclinic form was discovered (Uttiya et al, 2014), with the triclinic reported later (Moret & Gavezzotti, 2022).…”
Section: Database Surveymentioning
confidence: 68%
“…10 The formations of Herringbone structures are guided by solvent, 11 host−guest interactions, 12 effect of substituents, 13 and stimuli. 14 Stacking among the phenyl rings occur in several ways such as edge-to-face, face-to-face, or oblique types, as illustrated in Figure 1a. 15 It may be seen that the face-to-face parallel molecules either having eclipsed (Figure 1a (iii) or partly eclipsed (Figure 1a (vi)) geometries may be further arranged in different ways at translated positions in the case of eclipsed pairs, or as in a uni-directional manner (Figure 1a (vii)) or in bi-directions (Figure 1a (viii)).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting energy/structure landscape has intrinsic valuable information even if the holy Grail of exact crystal structure prediction is not attained. Having a plausible crystal structure, one can proceed to simulate surface properties and crystal morphologies, [16] important for stability and bioavailability, or to derive lattice vibrations and other thermodynamic, spectroscopic and heat conduction properties, important for materials science, by dedicated and extremely efficient downstream software [17] . These properties may change in different polymorphs, but any plausible structure can give an order‐of‐magnitude estimate and a preliminary idea of what one can expect from a given material.…”
Section: Introductionmentioning
confidence: 99%